Strontium Substituted Tricalcium Phosphate Bone Cement: Short and Long‐Term Time‐Resolved Studies and In Vitro Properties. Issue 21 (27th June 2022) - Rau, Julietta V.; Fadeeva, Inna V.; Forysenkova, Anna A.; Davydova, Galina A.; Fosca, Marco; Filippov, Yaroslav Yu.; Antoniac, Iulian V.; Antoniac, Aurora; D'Arco, Annalisa; Di Fabrizio, Marta; Petrarca, Massimo; Lupi, Stefano; et al.
Abstract: Due to a significant influence of strontium (Sr) on bone regeneration, Sr substituted β‐tricalcium phosphate (Sr‐TCP) cement is prepared and investigated by short‐ and long‐term time‐resolved techniques. For short‐term investigations, energy‐dispersive X‐ray diffraction, infrared spectroscopy, and, for the first time, terahertz time‐domain spectroscopy techniques are applied. For long‐term time‐resolved studies, angular dispersive X‐ray diffraction, scanning electron microscopy, mechanical tests, and behavior in Ringer solution are carried out. After 45 min of the cement setting, the Sr‐TCP phase is no longer detectable. During this time period, an appearance and constant increase of the final brushite phase are registered. The compressive strength of the Sr‐TCP cement increases from 4.5 MPa after 2 h of setting and reaches maximum at 13.3 MPa after 21 d. After cement soaking for 21 d in Ringer solution, apatite final product, with an admixture of brushite and TCP phases is detected. The cytotoxicity aspects of the prepared cement are investigated using NCTC 3T3 fibroblast cell line, and the cytocompatibility—by human dental pulp mesenchymal stem cells. The obtained results allow to conclude that the developed Sr‐TCP cement is promising for biomedical applications for bone tissue. Abstract : Hardening process of Sr substituted β‐tricalcium phosphate (Sr‐TCP) cement is monitored during short‐ and long‐time scale measurements. Nonlinear, oscillatory behavior characterizes the entire hardening process, until the final conversion into dicalcium phosphate dihydrate (DCPD). Soaking in Ringer solution leads to the formation of the apatite phase. Sr‐TCP cement promotes dental pulp human mesenchymal stem cells proliferation and their mass augmentation.